STRATEGI MENINGKATKAN PENGELOLAAN ARSIP DALAM PERSPEKTIF KEPEMIMPINAN TRANSFORMASIONAL - Annisa Pratiwi; Citra Risma Ramadhani; Hafis Zurachman Hidayat; Muhammad Agastya Haryanto; Siswadi (STKIP Subang, 2026)
Effective archive management becomes a prerequisite for accountable, transparent, and high-performing organizational governance. However, many organizations still face issues of low archival order, weak procedural discipline, and minimal utilization of archival technology, which hinder service and decision-making. In this context, transformational leadership is seen as having a strategic role in promoting changes in attitude, strengthening commitment, and innovation in archival management practices.This article aims to analyze strategies for improving archive management through a transformational leadership approach, focusing on the dimensions of ideal influence, inspirational motivation, intellectual stimulation, and individual consideration relevant to archival management practices. The research was conducted using literature review methods and normative analysis of archival frameworks as well as studies related to transformational leadership.The analysis results show that the effectiveness of archive management is determined not only by technical aspects but also by leadership styles that can build a shared vision, provide role models, develop archival staff competencies, and encourage sustainable use of technology. This article recommends strengthening the role of transformational leadership as the foundation for formulating integrated, adaptive archive management strategies that are oriented toward improving organizational performance. Keywords: transformational leadership, archive management, records management, organizational strategy.